Bernie Sanders’ Legacy as an Educator (AmeriQuests, 2022)
In this essay, I unpack what I believe to be Bernie Sanders' lasting impact from his long career in politics: educating the public, from his days as a documentary filmmaker to his most recent efforts to become President of the United States.